A strategy for solving the non symmetries arising in nonlinear consolidation of partially saturated soils - Di Rado, Héctor Ariel (2015)
Fil: Di Rado, Héctor Ariel. Universidad Nacional del Nordeste. Facultad de Ingeniería; Argentina.